Legalizing sex : sexual minorities, AIDS, and citizenship in India - Lakkimsetti, Chaitanya (New York : New York University Press, 2020)
This original ethnographic research explores the relationship between the HIV/AIDS epidemic and the rights-based struggles of sexual minorities in contemporary India. Sex workers, gay men, and transgender people became visible in the Indian public sphere in the mid-1980s when the rise of HIV/AIDS became a frightening issue. The Indian state started to fold these groups into national HIV/AIDS policies as 'high-risk' groups in an attempt to create an effective response to the epidemic. Lakkimsetti argues that over time the crisis of HIV/AIDS effectively transformed the relationship between sexual minorities and the state from one that was focused on juridical exclusion to one of inclusion.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 3, 2020).
Keywords: Sexual minorities -- Legal status, laws, etc. -- India; Sexual minorities -- Political activity -- India; Transgender people -- Legal status, laws, etc. -- India; Transgender people -- Political activity -- India; Sex workers -- Legal status, laws, etc. -- India; Sex workers -- Political activity -- India; AIDS (Disease) -- Patients -- Legal status, laws, etc. -- India; Law; Laws of specific jurisdictions & specific areas of law